Proses Produksi Program Talkshow “Prime Talk” di Metro TV - Happy Prasetyawati; Feraturan Karmelin (Inter Komunika, 2022)
The program "Prime Talk" on Metro TV has its own uniqueness. This program is a news talk show program that in one episode only discusses one problem topic. "Prime Talk" will invite speakers related to the material being discussed.Usually the invited speakers can be from various circles depending on the material to be discussed. Many preparations are carried out in the production process starting from the pre-production to post-production stages.Researchers use the concept proposed by Gerald Millerson and Owen in the book “ Television Production “. In this study, a post-positivistic paradigm was used with a qualitative approach with descriptive methods and using data collection techniques with interviews and observations. Researchers interviewed one Key Informant and one Informant. This research resulted in Prime talk conducting the production process from pre-production, starting from the search for ideas, live production stages and post-production stages performed with Live editing. Keywords : Production process, production stages, prime talk, Metro TV